2009
DOI: 10.1021/jp811494p
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Antimicrobial Peptides into Membranes: A Combined Liquid-State NMR and Molecular Dynamics Study of Alamethicin in DMPC/DHPC Bicelles

Abstract: Detailed insight into the interplay between antimicrobial peptides and biological membranes is fundamental to our understanding of the mechanism of bacterial ion channels and the action of these in biological host-defense systems. To explore this interplay, we have studied the incorporation, membrane-bound structure, and conformation of the antimicrobial peptide alamethicin in lipid bilayers using a combination of 1H liquid-state NMR spectroscopy and molecular dynamics (MD) simulations. On the basis of experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 51 publications
5
56
0
2
Order By: Relevance
“…The second peptide, alamethicin, is produced by the fungus Trichoderma viride [30], [31] and displays antibiotic properties similarly to novicidin. This peptide presumably forms a barrel-stave type arrangement at high concentration when added to neutral and charged lipid bilayers [18], [30], [32][39]. The results support these two different proposed modes of action for the two peptides and reveal details of the AMP's paths to membrane disruption and pore formation through characterization of the low-P:L states.…”
Section: Introductionsupporting
confidence: 58%
“…The second peptide, alamethicin, is produced by the fungus Trichoderma viride [30], [31] and displays antibiotic properties similarly to novicidin. This peptide presumably forms a barrel-stave type arrangement at high concentration when added to neutral and charged lipid bilayers [18], [30], [32][39]. The results support these two different proposed modes of action for the two peptides and reveal details of the AMP's paths to membrane disruption and pore formation through characterization of the low-P:L states.…”
Section: Introductionsupporting
confidence: 58%
“…The monolayer structure and small curvature radius of micelles can cause peptides and proteins to adopt incorrectly folded conformations or to aggregate (118). Recently, discoidal micelles or bicelles have been used in NMR spectroscopy of both membrane peptides and proteins (112, 118122). Generally, bicelles are formed by long-chain phospholipids (DMPC, DMPG) and amphiphilic molecules such as CHAPSO, or a short-chain lipid, such as DHPC.…”
Section: Bacterial Membrane Composition and Membrane Mimicking Sysmentioning
confidence: 99%
“…23 Dittmer et al reported a combined NMRÀMD study of alamethicinÀ lipid interactions. 24 Sengupta et al observed significant amounts of disorder in toroidal pore structures in another MD study of AMPs. 25 Jean-Francois et al 26 also investigated the roles of electrostatic effects on AMP action.…”
Section: ' Introductionmentioning
confidence: 97%